EXPLORING THE INFLUENCE OF INTERACTIVE LEARNING MEDIA ON THE NUMERICAL ABILITY OF EARLY CHILDHOOD LEARNERS AT PAUD GEMILANG TANGERANG SELATAN - Rahayu, Suharni (BAIK Publishers, 2025)
This qualitative study explores the influence of interactive learning media on the numerical ability of early childhood learners at PAUD Gemilang. The research addresses the problem of low motivation and understanding in early numeracy among young children and aims to investigate how interactive media impact children's engagement, comprehension, and skill development in numerical concepts. Guided by constructivist learning theories and employing semi-structured interviews, observations, and document analysis, the study gathered rich qualitative data from both learners and educators. Findings reveal that interactive media significantly enhance children's motivation and participation by providing multi-sensory, playful, and self-paced learning experiences. Educators observed clearer understanding of numerical concepts and faster acquisition of counting and number recognition skills in children using interactive media compared to conventional methods. Challenges related to digital literacy and technical issues were mitigated by guided support and institutional backing. This study concludes that interactive media is an effective pedagogical tool for early numeracy development, offering recommendations for educators and PAUD institutions to optimize media use in classrooms. The results contribute to advancing educational practices in early childhood settings by integrating technology-enhanced learning tailored to young learners’ needs.